Air Quality Monitoring in Briquette Industrial Environments through Air Particle Detection Systems - hiron, Nurul; Faridah, Linda; Rahayu, Andri Ulus (Institut Teknologi Nasional, Bandung, 2024)
Air is the most basic need for the survival of living things, especially humans. Briquetting plants are one of the industries that produce airborne particles harmful to human health and the surrounding environment. These particles can cause respiratory problems and serious illnesses if not properly detected and controlled. Therefore, an air particle detection system is indispensable for monitoring air quality in the factory environment. PT Arkelindo Bara Sejahtera, as a company engaged in the manufacture of briquettes, has a negative impact on the environment, especially air pollution due to the carbonization process that produces smoke and dust. The implementation of this community service activity aims to improve air quality in the briquette industry environment through the implementation of an air particle detection system. This activity includes socialization about the dangers of air particles, training on the use of detection devices, and filling out questionnaires to evaluate participants' understanding. The results of this activity show that the air quality in the factory environment is still poor with high Air Quality Index (AQI) values, mainly caused by the carbonization process. However, this activity succeeded in raising the awareness of the factory staff on the importance of air quality monitoring and providing concrete recommendations to reduce particle emissions, including the use of cleaner fuels and improving the efficiency of the carbonization process. Thus, it is hoped that this activity can help prevent more severe air pollution in the future and protect the health of the surrounding community.